The U.S.-China Trade War : The Effects of Chinese Retaliatory Tariffs on Soybean Trade - Basiubina, Polina; Bolotov, Ilya; Pantea, Smaranda; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2021)
In summer 2018, the Trump administration began imposing tariffs on Chinese exports, further prompting retaliation from China, which consequently sparked the trade war between the world’s two largest economies. Escalated trade conflict between the United States and China over the course of 2018 has also drawn a great deal of attention of those directly involved in trading with China and highly dependent on this market. Disrupted trade relationship between the two economies was particularly devastating for U.S. agriculture, especially soybeans, since China has been the largest export market for this commodity for the past decade. Accordingly, the aim of the thesis is to identify the effects of the U.S.-China trade war on trade in soybeans. In order to explore the effects, the author will utilize quantitative methods of investigation by analyzing secondary quantitative data. Given the strong geographic concentration of soybean trade, the major disruptions caused by the trade war might, in the long term, reduce the trade share of the United States in the global soybean market and result in Brazil becoming the leading supplier of soybeans to China, consequently expanding its market share in China. The thesis starts by investigating the origins of trade tensions between the United States and China. Then it examines tariff escalation between the countries, focusing on agriculture. Next, it analyzes changes in soybean trade following Chinese retaliatory tariffs. Finally, it reviews the Phase One trade deal.
Vedoucí práce: Ilya Bolotov
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses